Efectividad de filgrastim en el tratamiento de neutropenia inducida por taxanos, en pacientes con cáncer de mama atendidos en el Instituto Regional de Enfermedades Neoplásicas –Trujillo, Octubre 2016- Octubre 2017 - Ibañez vega, Kelly Maruja (2018)
In the present research work absolute neutrophil count has been used as a criterion of effectiveness of filgrastim in the treatment of taxane induced neutropenia in patients with breast cancer treated on an outpatient basis at the Regional Institute of Neoplastic Diseases from Trujillo, Peru. We included the clinical records of 60 patients whose inclusion criteria included the development of neutropenia after receiving chemotherapy with paclitaxel or docetaxel, during the period October 2016 to October 2017. At the beginning of the treatment, the number was recorded of clinical history, sex, age, height, weight, clinical stage of cancer, chemotherapeutic schedule, dates of administration of chemotherapy, number of cycles programmed and received, as well as the value of absolute neutrophil count. At the control appointment 15 days after chemotherapy, or in some admission to the Emergency Service due to the presence of infection or fever, the value of the absolute neutrophil count was again recorded to determine if there was an episode of neutropenia. In patients with any level of neutropenia, it was verified if they received filgrastim as treatment; the value of the absolute neutrophil count greater than or equal to 2000 / mm3 determined whether there was remission of neutropenia. Filgrastim was effective in 80% of patients who developed neutropenia induced by taxanes in patients with breast cancer; in addition, in the Chi square statistical test, p <0.05 was obtained